2017
DOI: 10.1155/2017/8192150
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Crohn’s Disease: An Approach to an Uncommon but Important Cutaneous Disorder

Abstract: Objective. To provide physicians with a clinical approach to metastatic Crohn's disease (MCD). Main Message. Metastatic Crohn's disease, defined as skin lesions present in areas noncontiguous with the gastrointestinal tract, is the rarest cutaneous manifestation of Crohn's disease. MCD lesions vary in morphology and can arise anywhere on the skin. MCD presents equally in both sexes and across age groups. Cutaneous findings may precede, develop concurrently with, or follow gastrointestinal involvement. A detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
31

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(128 citation statements)
references
References 61 publications
(117 reference statements)
1
70
0
31
Order By: Relevance
“…Cutaneous CD affects male and female individuals of all ages . It has been reported that 22%‐44% of patients with CD have cutaneous symptoms at some point in their disease course, and 7%‐24% of children have extraintestinal manifestations of CD . It is likely that the true incidence of cutaneous CD, and specifically MCD, is underestimated because of lack of reporting and misdiagnosis.…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…Cutaneous CD affects male and female individuals of all ages . It has been reported that 22%‐44% of patients with CD have cutaneous symptoms at some point in their disease course, and 7%‐24% of children have extraintestinal manifestations of CD . It is likely that the true incidence of cutaneous CD, and specifically MCD, is underestimated because of lack of reporting and misdiagnosis.…”
Section: Epidemiologymentioning
confidence: 99%
“…The most common presentation of MCD is genital swelling . Other areas of involvement include the extremities, intertriginous zones, legs, and trunk, with the breast, nipple, ear, and umbilicus reported less often . Some lesions have been reported to be completely asymptomatic, whereas others are pruritic, tender, and painful.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 3 more Smart Citations